Characterization of newly established Pralatrexate-resistant cell lines and the mechanisms of resistance - Oiwa, Kana (BMC Cancer, 2021)
BACKGROUND: Pralatrexate (PDX) is a novel antifolate approved for the treatment of patients with relapsed/refractory peripheral T-cell lymphoma, but some patients exhibit intrinsic resistance or develop acquired resistance. Here, we evaluated the mechanisms underlying acquired resistance to PDX and explored potential therapeutic strategies to overcome PDX resistance. METHODS: To investigate PDX resistance, we established two PDX-resistant T-lymphoblastic leukemia cell lines (CEM and MOLT4) through continuous exposure to increasing doses of PDX. The resistance mechanisms were evaluated by measuring PDX uptake, apoptosis induction and folate metabolism-related protein expression. We also applied gene expression analysis and methylation profiling to identify the mechanisms of resistance. We then explored rational drug combinations using a spheroid (3D)-culture assay. RESULTS: Compared with their parental cells, PDX-resistant cells exhibited a 30-fold increase in half-maximal inhibitory concentration values. Induction of apoptosis by PDX was significantly decreased in both PDX-resistant cell lines. Intracellular uptake of [(14)C]-PDX decreased in PDX-resistant CEM cells but not in PDX-resistant MOLT4 cells. There was no significant change in expression of dihydrofolate reductase (DHFR) or folylpolyglutamate synthetase (FPGS). Gene expression array analysis revealed that DNA-methyltransferase 3β (DNMT3B) expression was significantly elevated in both cell lines. Gene set enrichment analysis revealed that adipogenesis and mTORC1 signaling pathways were commonly upregulated in both resistant cell lines. Moreover, CpG island hypermethylation was observed in both PDX resistant cells lines. In the 3D-culture assay, decitabine (DAC) plus PDX showed synergistic effects in PDX-resistant cell lines compared with parental lines. CONCLUSIONS: The resistance mechanisms of PDX were associated with reduced cellular uptake of PDX and/or overexpression of DNMT3B. Epigenetic alterations were also considered to play a role in the resistance mechanism. The combination of DAC and PDX exhibited synergistic activity, and thus, this approach might improve the clinical efficacy of PDX. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12885-021-08607-9.